2019
DOI: 10.1016/j.jafrearsci.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Drivers, patterns and velocity of saltwater intrusion in a stressed aquifer of the East African coast: Joint analysis of groundwater and geophysical data in southern Kenya

Abstract: Fresh groundwater resources in coastal East Africa are crucial for the region's socioeconomic development but are under threat of salinization caused by changes in recharge patterns and increasing abstraction. With the aim of establishing the drivers behind saltwater intrusion and its current spatial extent, we studied the Kenyan South Coast aquifer, a representative, strategic aquifer under increased pressure. Investigations included electrical resistivity tomography (ERT) surveys and in-situ groundwater meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…A recent study on coastal groundwater in Bhola District, Bangladesh, reported an average EC of 588.15 µS/cm [46], indicating a notable difference between the two reports. However, the EC values observed in this study align with those found in coastal aquifers of Southern Kenya [47], Western Cape Province, South Africa [48], and South [49]. Typically, fresh groundwater unaffected by saltwater intrusion exhibits mild salinity and, thus, low EC values.…”
Section: Physical Parameterssupporting
confidence: 82%
“…A recent study on coastal groundwater in Bhola District, Bangladesh, reported an average EC of 588.15 µS/cm [46], indicating a notable difference between the two reports. However, the EC values observed in this study align with those found in coastal aquifers of Southern Kenya [47], Western Cape Province, South Africa [48], and South [49]. Typically, fresh groundwater unaffected by saltwater intrusion exhibits mild salinity and, thus, low EC values.…”
Section: Physical Parameterssupporting
confidence: 82%
“…Untreated sewerage discharged or leakage of organic and microbial pollutants to water bodies also contribute to the deterioration of water quality in many countries resulting in several public health threats and disease outbreaks in SSA (Gumbo et al, 2016; Houéménou et al, 2020). Seawater intrusion particularly in coastal areas is another source of shallow groundwater contamination, rendering it undrinkable, and not suitable for irrigation (Oiro & Comte, 2019; Takem et al, 2015). Emerging organic contaminants have equally been detected in wastewater, surface water and groundwater wells across many countries (Gwenzi & Chaukura, 2018; Sorensen et al, 2015).…”
Section: Water Security Challenges Facing Sub‐saharan Africamentioning
confidence: 99%
“…In Northeastern Tunisia, as the result of overexploitation of the coastal Ras el Jabel aquifer the range of groundwater salinity has increased from 1.5-4 g/L in 1969 to 5-10 g/L in the 1990s (Khater, 2019). Well fields in coastal southern Kenya show a gradual increase from less than 400 S/Cm in the 1970s to 1100 S/cm in 2017 (Oiro and Comte, 2019). In Djibouti a similar increase in the salinity of coastal aquifers has been observed (Houssein and Jalludin, 1996).…”
Section: Rock Dissolutionmentioning
confidence: 67%